2013
DOI: 10.2147/mder.s47206
|View full text |Cite
|
Sign up to set email alerts
|

Power port contrast medium flushing and trapping: impact of temperature, an in vitro experimental study

Abstract: PurposeThe use of totally implantable venous access devices (TIVADs) certified as “high pressure resistant” or “power port” has begun to spread worldwide as a safe procedure for power contrast injection. Owing to the thermo-rheological properties of the contrast media, the primary aim of this work is to present an in vitro experimental impact study concerning the impact of the temperature level on flushing efficiency after contrast medium injection. Moreover, we report experimental data that confirms the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The flushing of venous catheters is a complex process, where convection and diffusion are coupled with chemical interactions associated with protein adhesion and disadhesion 9. Moreover, the flushing efficacy could be enhanced by heating up the flushing solution to body temperature, as shown by Guiffant et al31…”
Section: Discussionmentioning
confidence: 99%
“…The flushing of venous catheters is a complex process, where convection and diffusion are coupled with chemical interactions associated with protein adhesion and disadhesion 9. Moreover, the flushing efficacy could be enhanced by heating up the flushing solution to body temperature, as shown by Guiffant et al31…”
Section: Discussionmentioning
confidence: 99%
“…1B), with the orientation of the bevel opposite to the catheter outlet. This type of geometry has been used in previous studies (14, 16, 17) and has been found to be the best configuration for flushing efficacy. Figures 1C, D, E and F show the situation when introducing a BFC.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Such an effect is clearly missing in the situation depicted in Figure 2B with a bevel-free extremity: the outlet flow exhibits a cylindrical symmetry leading to a circular spreading of the flow. The interaction of the outlet stream from a beveled extremity with the bottom and side walls of the port provides the best conditions to flush and use the port chamber (14, 16, 17). To include the reservoir's design as a contributing factor in flushing efficiency, we tested lines of flow in both curved side wall and straight wall ports.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…For more than 20 years, totally implantable venous access ports have been used in patients with cancer or chronic diseases. 1,2 Patients with a totally implantable venous access port often undergo a computed tomography (CT) scan with contrast media (CM) injection for clinical examination or follow-up, usually with easy and safe peripheral IV access. However, in some patients, peripheral IV access is difficult, and the implanted venous port is the only access route.…”
Section: Introductionmentioning
confidence: 99%